2021
DOI: 10.1142/s2529732521400058
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Water and Salt Suppress Respiratory Droplet Generation and COVID-19 Incidence and Death on US Coastlines

Abstract: Dry air alters salt and water balance in the upper airways and increases the risks of COVID-19 among other respiratory diseases. We explored whether such upper airway variations in salt and water balance might alter respiratory droplet generation and potentially contribute to observed impacts of airway hydration on respiratory disease. In a randomized 4-arm study of 21 healthy human subjects we found that the breathing of humid air, the wearing of cotton masks, and the delivery of (sodium, calcium, and magnesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 38 publications
4
12
0
Order By: Relevance
“…Explaining this unexpected increase of the concentration of aerosol particles during exercise is a challenge for future studies. Possible factors include changes in the velocity and type (i.e., turbulent versus laminar) of gas flow, changes of the composition of the liquids that line the airways, and changes in the hydration status of the airways ( 20 , 21 ). Thus, besides exercise intensity, the airway dehydration that was potentially caused by the endurance exercise and higher ventilation rates could have contributed to the increased aerosol particle emission.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Explaining this unexpected increase of the concentration of aerosol particles during exercise is a challenge for future studies. Possible factors include changes in the velocity and type (i.e., turbulent versus laminar) of gas flow, changes of the composition of the liquids that line the airways, and changes in the hydration status of the airways ( 20 , 21 ). Thus, besides exercise intensity, the airway dehydration that was potentially caused by the endurance exercise and higher ventilation rates could have contributed to the increased aerosol particle emission.…”
Section: Discussionmentioning
confidence: 99%
“…A further limitation is that possible changes of the hydration status of the subjects were not assessed, as the hydration status can affect aerosol particle emission ( 20 , 21 ). Subjects were allowed to drink water ad libitum in the 3 h before the test to avoid pretest dehydration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The breathing of dry air has recently been observed to amplify upper-airway respiratory droplet generation 41 on normal tidal breathing. Hydration of the upper airways by the breathing of humid air, the wearing of a face mask, or the direct delivery of isotonic or hypertonic saline droplets targeted to the posterior of the nose, larynx and trachea 42 with mean droplet sizes around 8-12 μm reduces respiratory droplet generation to similar degrees and durations 41 . Beyond the consequences of hydration on glottal aperture and laryngeal-jet features-hydration of the larynx increases glottal aperture and reduces phonation threshold pressure 43 , the fluid mechanical basis of laryngeal hydration protocols for singers 43 -hydration alters respiratory droplet formation by volume expansion of the airway lining fluid.…”
mentioning
confidence: 99%
“…At the same temperature but higher humidity around 50%, transmission efficiency was significantly reduced 34 . Recent studies on COVID‐19 in humans revealed that hydration of the upper airways diminishes respiratory droplet generation and may reduce the risks of respiratory infectious disease incidence and symptoms 35,36 . Thus, those combined host and environment effects due to low humidity might be causative for respiratory infectious diseases in the low humidity season.…”
Section: Discussionmentioning
confidence: 99%